A research note: Effect of Hofmeister salts on meat iridescence in cooked pork. (March 2023) - Ruedt, Chiara; Gibis, Monika; Weiss, Jochen
The effect of Hofmeister salts (NaCl, NaSCN, Na2 SO4, KCl, LiCl, CaCl2 ) on surface iridescence in cooked pork was investigated. Strongest iridescence occurred in samples treated with NaSCN, NaCl and KCl. Control samples and LiCl, CaCl2 and Na2 SO4 treatments showed weaker iridescence. However, differences between KCl and LiCl, CaCl2 and Na2 SO4 were not statistically significant (p > 0.05). Nevertheless, a tendency of chaotropic salts (NaSCN, NaCl, KCl) to cause stronger iridescence was noted that might be explained with a more effective solubilization of myofibrillar proteins (MPs), reducing incoherent scattering from the myofibrils and thus enhancing multilayer interference.